Prevalence and Risk Factors of Dance Injury During COVID-19: A Cross-Sectional Study From University Students in China - Dang, Yanan; Koutedakis, Yiannis; Chen, Rouling; Wyon, Matthew A. (Frontiers in Psychology, 2021)
Objectives: Although COVID-19 has transformed dancers’ training environment worldwide, little is known on how this has affected injury prevalence, causes and risk factors. Methods: An online investigation was conducted (September to November 2020) involving Chinese full-time dance students, which covered two 6-month periods just before and during the first COVID-19 lockdown. Results: 2086 students (19 ±2.4yrs) responded. Injury prevalence before lockdown dropped from 39.6% to 16.5% during lockdown (p<0.01). A significant increase in injury severity during lockdown was noted with a 4.1% increase in moderate to severe injuries (p<0.05). During the lockdown, injuries of the lower back, feet and shoulders decreased significantly (p<0.01), but the knees, ankles and groin/hip-joint injuries remained the same. Recurrence of old injury and fatigue remained as the top 2 perceived causes of injury between the two periods with unsuitable floor (p<0.01), cold environment (p<0.05) and set/props (p<0.05) increasing. Students’ fatigue degree decreased (p<0.01) and sleep hours increased (p<0.01) during lockdown. Binary logistic regression analysis indicated that dance injury was associated with fatigue, hours of sleep, and action taken if they suspected an injury during lockdown (p<0.05), but was only related to time set aside for cool-down and age before lockdown (p<0.05). Conclusion: Although the injury prevalence dropped significantly during the first COVID-19 lockdown in Chinese dance students, the main dance injury characteristics remained the same. Decreased fatigue and longer sleep hours could explain the aforementioned drop in injury prevalence during the lockdown.